Uniform limit power-type function spaces - Chuanyi Zhang; Weiguo Liu (International Journal of Mathematics and Mathematical Sciences)
To answer a question proposed by Mari in 1996, we propose 𝒰ℒ𝒫α(ℝ+), the space of uniform limit power functions. We show that 𝒰ℒ𝒫α(ℝ+) has properties similar to that of 𝒜𝒫(ℝ+). We also proposed three other limit power function spaces.